Analysis of the problems of synthesis of new nanocrystalline chalcogenide materials for thermoelectric generators and sodium-ion batteries - М.М. Кубенова; К.А. Кутербеков; М.Х. Балапанов; Р.Х. Ишембетов; К.Ж. Бекмырза; А.М. Кабышев; Ш. Афрозе; Р.Ш. Палымбетов; Ж.А. Мұханова; Е. Шукалов (Қарағанды университетінің хабаршысы. Физика сериясы)
The paper analyzes the problems of the synthesis of new nanocrystalline chalcogenide materials for thermoelectric generators and sodium-ion batteries. The objectives of the synthesis will determine the best method to use to create chalcogenide materials for electrodes in real-world applications. The method of direct solid-phase reaction in a vacuum or in an environment of pure inert gas is the most effective way to generate novel chalcogenide materials in tiny amounts for the investigation of physicochemical and other features.With this approach, which is more dependable, it is feasible to produce a pure result free of contaminants that are inescapable when working with other solvents and precursors. Additionally, in a consistent synthesis regime, it is differentiated by the stability of the acquired attributes of the compounds. Synthesis modes, reagents, and post-processing depend on the specific material. The method of synthesizing alloys in a melt media made up of a combination of potassium and sodium hydroxides is one of the key techniques employed in the present research. The melting point drops to 165 °C at a certain ratio of the concentrations of these hydroxides, allowing for the execution of salt exchange processes in the melt. The size of the resultant chalcogenide particles can be reduced to a few nanometers by lowering the synthesis temperature, adding water, and shortening the annealing period.